Improvement of Beginning Reading Ability in Class V Dyslexic Students through the Silaba Method at Jombang 05 Public Elementary School - Risky Amelia; Ana Rafikayati; Amelia Rizky Idhartono (Universitas PGRI Adi Buana Surabaya, 2023)
The objective of this research is to look into the inclusion of children with neurological diseases in Indian education. According to the research, a substantial proportion of children in India have neurological disorders, and they frequently face barriers to education. The study examines the current situation of education for children with neurological problems in India, as well as the policies and laws that regulate their education. The review also looks at the difficulties that these children, their families, and educators have had in implementing inclusive education. Lastly, the report explores interventions and techniques that can help children with neurological disorders be included in Indian education settings with a concerted effort from all stakeholders involved in the education process.